The Pol Pot regime : race, power, and genocide in Cambodia under the Khmer Rouge, 1975-79 - Kiernan, Ben (Yale University Press, 2008)
This edition of Ben Kiernan's account of the Cambodian revolution and genocide includes a new preface that takes the story up to 2008 and the UN-sponsored Khmer Rouge tribunal. Kiernan's other books include 'Blood and Soil: A World History of Genocide and Extermination from Sparta to Darfur' and 'How Pol Pot Came to Power'.